Neželjeni kardiovaskularni događaji nakon ugradnje Absorb biorazgradivog koronarnog stenta: rezultati jednogodišnjeg kliničkog praćenja - Šobot, Tanja; Šobot, Nikola; Bajić, Zorislava; Ponorac, Nenad; Babić, Rade (Scripta Medica, 2021)
Background/Aim: Bioresorbable vascular scaffold (BVS) represents a novel generation of intracoronary devices designed to be fully resorbed after healing of the stented lesion, delivering antiproliferative drug to suppress restenosis, providing adequate diameter of the coronary vessel and preserving the vascularendothelial function. It was supposed that BVS will reduce neointimal proliferation and that their late bioresorption will reduce the negative effects of traditional drug-eluting stents, including the late stent thrombosis, local vessel wall inflammation, loss of coronary vasoreactivity and the need for the long-termdual antiplatelet therapy. The purpose of this research was to investigate efficacy and safety of Absorbeverolimus-eluting BVS implantation and the prevalence of major adverse cardiovascular events (MACE) at the mid-term follow-up.Methods: The study encompassed 42 patients selected for BVS implantation and fulfilling inclusion criteria - 37 male and 5 female - admitted to the Dedinje Cardiovascular Institute, Belgrade, Serbia over the one-year period (from January 2015 to January 2016) for percutaneous coronary intervention (PCI). Coronaryvessel patency before and after stenting was assessed by the Thrombolysis in Myocardial Infarction flow (TIMI) grades. After the index PCI procedure with BVS all patients were clinically followed byregular (prescheduled or event-driven) visits during the next 12-month period.Results: In the intention-to-treat analysis, all Absorb BVS procedures were successful, without the need for conversion to other treatment modalities. The complete reperfusion (TIMI flow grade 3) after the intervention was established in 97.6 % of patients and 100 % of them achieved the TIMI flow grade ≥ 2.The presence of angina pectoris was reduced significantly by the BVS procedure: stable angina 57.1 % to 11.9 %, (p < 0.001) and unstable angina 31 % to 0 %, respectively (p < 0.001). After the one-year follow-up, the MACE rate was 11.9 %. Myocardial infarction occurred in 4.8 % and the need for PCI reintervention in 2.4 % of cases (not influenced by the gender or the age of patients). There were 4 cases of death (all patients were older and had lower values of left ventricular ejection fraction).Conclusion: The results of the current research demonstrated a high interventional success rate of the Absorb BVS implantation, followed by the early improvement of the anginal status. However, that was not translated into the favourable mid-term clinical outcomes, opening debate about the current status ofAbsorb BVS and the need for future refinements of stent design and implantation techniques.